Reports of foreign societies of awarding medals to the American Arctic explorers, Kane, Hayes, Hall. - YA Pamphlet Collection (Library of Congress) DLC; United States Naval Observatory. ([Washington D.C.?] : U.S. Naval Observatory, 1876)
Mode of access: Internet.